Conceptualizing legal harmonization approach In Malaysia. - Mohamad Yunus, Mohamad Ismail (Faculty of Law, Universitas Lampung, 2023)
Legal harmonization is a fundamental notion of comparative law that has been on the international and national agendas for the last decade. Harmonization, which derives from the word “harmony,” has a variety of meanings, one of which, in the perspective of the discussion of this topic, is the readiness and the openness to recognize, acknowledge, adopt, or accept anything produced, practiced by or originating from man-made laws, modern secular traditions, customs and usages, cultures, societies, systems or institutions which is considered to be in “harmony” with or not opposed to the worldview, principles, values, teachings, and norms of Islam. Thus, the conceptualizing approach of harmonization of legal knowledge and education is a process of actualizing the divine imperatives in the legal arena. In Malaysia, several endeavors have sought the similarity between legal rules from different jurisdictions; however, their achievements remain contested since there is no comprehensive understanding of the nature and extent of harmonization. Thus, this article examines different facets of harmonization by considering it a legal phenomenon instead of a distinct process of drafting similar rules. Adopting a comprehensive understanding of harmonization as a legal phenomenon may help better assess the strengths of the implementation processes and formulate adequate new legal endeavors.